Trends in knee osteoarthritis prevalence over a 10-year period in Japan: The ROAD study 2005–2015 - Gaku Tanegashima; Toshiko Iidaka; Shigeyuki Muraki; Chiaki Horii; Hiroyuki Oka; Hiroshi Kawaguchi; Kozo Nakamura; Toru Akune; Sakae Tanaka; Noriko Yoshimura (Osteoarthritis and Cartilage Open)
Objective: This study aimed to clarify the trends in the prevalence of knee osteoarthritis (OA) and symptomatic knee OA among the general population using population-based cohort data from baseline and a survey 10 years later. Design: The baseline survey of the Research on Osteoarthritis/Osteoporosis Against Disability (ROAD) study was conducted from 2005 to 2007; 3040 participants (1061 men and 1979 women; mean age 70.3 years) completed all OA examinations, including a questionnaire of medical information in the present/past and radiographic examination. The fourth survey was performed from 2015 to 2016; 2893 individuals (895 men and 1998 women, mean age 68.9 years) completed assessments identical to those at the baseline survey. Knee OA was defined using the Kellgren–Lawrence grading system. Results: The prevalence of knee OA was 54.6 ​% (men, 42.0 ​%; women, 61.5 ​%) at the baseline survey and 39.3 ​% (men, 26.9 ​%; women, 44.9 ​%) at the fourth survey, with a significant decrease (p ​< ​0.0001). The prevalence of symptomatic knee OA was 24.3 ​% (men, 16.9 ​%; women, 28.3 ​%) at the baseline survey and 20.6 ​% (men, 14.2 ​%; women, 23.5 ​%) at the fourth survey, showing a similar decrease (p ​< ​0.0001). Thus, the prevalence of knee OA and symptomatic knee OA was lower at the fourth survey than at the baseline survey (p ​< ​0.01). Conclusions: In the population-based survey with a 10-year interval, the prevalence of knee OA and symptomatic knee OA decreased significantly. This preferable change in OA may suggest rejuvenation in the current population and could contribute to a decrease in the occurrence of disabilities in the future.